DRM Paradigm: Evidence that Alzheimer's Patients Think of the Critical Lure as Often as Healthy Older Participants. - Gilet, Anne-Laure; Evrard, Christelle; Colombel, Fabienne (Experimental Aging Research)
Up to now, in the Deese-Roediger-McDermott (DRM) paradigm, the lower production of false memories in Alzheimer's disease has been explained in terms of non-activation of the critical lure. The aim of this study was to examine the critical lure activation process from items of DRM lists in Alzheimer's patients, using a free association task. Twenty-six young adults, 25 older adults, and 17 Alzheimer's patients performed a free association task with DRM words. Analyses indicated that Alzheimer's patients produced as many critical lures in the free association task as healthy older participants, but significantly fewer than younger participants. Our results suggest that the low production of critical lures in DRM tasks usually reported in Alzheimer's patients might not be due to a semantic deficit that prevents the activation of the critical lure.